Torsional strength analysis of universal joint’s ZP-11A due to yokes modification and materials - Hartono Yudo; Andi Setiawan; Ocid Mursid; Muhammad Iqbal (National Research and Innovation Agency, 2022)
The study examined the strength of the universal joint after it was loaded with torsion. It used different materials that can withstand tensile stress in accordance with accepted principles and made modifications to the yoke as a result of the topology optimization process. The topology optimization determined that the yoke's part needed to withstand load without changing its dimensions and minimize stress distribution. According to the results, the maximum shear stress on the spider of the original universal joint model made of JIS-SF590A steel was 84.57 MPa, the shear stress on the yoke component was 30.84 MPa, and the maximum von Mises was 341.1 MPa. As a result of using JIS-SF590A steel, yoke modification 3 has produced a reduction in shear stress of 12.97 % and a reduction in von Mises stress of 35.33 % from the original yoke. This is the most efficient design of yoke and also this modified yoke form provides a wider elevation angle and is easier to manufacture.